Analysing the Role of Visual Content in Increasing Attraction and Conversion in MSME Digital Marketing - Sunarso, Budi; Tusriyanto; Mustafa, Fahrina (PT. LITERASI SAINS NUSANTARA, 2023)
In the rapidly digitizing era, the business world, especially Micro, Small, and Medium Enterprises (MSMEs), undergoes significant changes in marketing strategies. Digital marketing has become a highly effective tool to enhance visibility and customer attraction. In this context, visual content plays a crucial role as a primary element in crafting digital campaigns. This research aims to analyze the role of visual content in enhancing attraction and conversion in MSMEs' digital marketing. The approach involves an in-depth exploration of literature through qualitative analysis, intending to achieve a comprehensive understanding of the subject from 2013 to 2023. The study results indicate that in the continually evolving digital marketing landscape, the role of visual content in supporting MSMEs is crucial. Visual content not only captures consumer attention but also builds brand identity, enhances engagement on social media, strengthens storytelling, simplifies product understanding, supports SEO, and ultimately increases conversion rates. By effectively designing and optimizing visual content, MSMEs can harness its full potential to grow and succeed in the digital market.